Identification of the first erm(B)-positive Campylobacter jejuni and Campylobacter coli associated with novel multidrug resistance genomic islands in Australia. (December 2020) - Wallace, Rhiannon L.; Bulach, Dieter; Valcanis, Mary; Polkinghorne, Benjamin G.; Pingault, Nevada; Stylianopoulos, Anastasia; Givney, Rodney C.; Glass, Kathryn; Kirka, Martyn D.
Highlights: First report of Campylobacter harbouring erm (B) in Australia. Campylobacter isolates from retail food products did not possess erm (B). In both cases, C. jejuni and C. coli were likely acquired in Southeast Asia. Multidrug resistance genotypes were identified in both erm (B)-positive isolates. Abstract: Objectives: This report describes the first identification of two Campylobacter isolates harbouring erm (B) in Australia. Methods: Two erm (B)-positive isolates, Campylobacter coli 18V1065H1 and Campylobacter jejuni 19W1001H1, were isolated from diarrhoeal faecal samples from two travellers who had recently returned from Southeast Asia. Isolates underwent whole-genome sequencing using an Illumina NextSeq system and were analysed with the Nullarbor pipeline. Antimicrobial resistance genes were identified using AMRFinderPlus and sequence types (STs) were determined by multilocus sequence typing and the PubMLST Campylobacter jejuni/coli typing scheme. Results: Besides erm (B), C. jejuni 19W1001H1 possessed six other resistance genes [ aad9, aadE, aph(3ʹ)-Illa, bla OXA-185, catA13 and tet (O)], the gyrA T86I mutation and the RE-CmeABC multidrug efflux pump variant. Campylobacter coli 18V1065H1 also possessed six resistance genes [ aad9, aadE, aph(3ʹ)-IIIa, bla OXA-61, sat4 and tet (O)] in addition to erm (B); however, this isolate lacked genetic evidence for resistance to fluoroquinolones (no gyrA mutation). The erm (B) locus differed between isolates and neither was identical to previously identified erm (B) multidrug resistance genomic island (MDRGI) types. Both erm (B)-bearing isolates belonged to novel sequence types: ST9967 ( C. jejuni 19W1001H1) and ST10161 ( C. coli 18V1065H1). Conclusions: This study detected the presence of erm (B) in Campylobacter for the first time in Australia. This novel mechanism of macrolide resistance is a major concern both for human and animal health and warrants close surveillance as macrolides are often the drug of choice for treating campylobacteriosis. The erm (B) gene is associated with several MDRGIs and dissemination of this resistance mechanism will likely limit treatment options for Campylobacter infections.